ASSESSMENT OF PHYSICO-CHEMICAL PROPERTIES OF SHALLOW WELL WATER IN KAWANGWARE LOCATION, NAIROBI CITY, KENYA - Beth Waithera Njiraini,; Dr. Ezekiel Ndunda,; Kamande, Peter Ngugi (IJRDO-Journal of Applied Science, 2020)
Limited of access to portable water is adversely affecting the public health in many developing countries worldwide. Kawangware Ward in Dagoretti North Constituency is one of the areas undergoing rapid expansion in population, economic growth and urbanization in Nairobi County. This has significantly increased the pressure on public water supply systems in the county. The aim of this study was to determine the quality of water from shallow wells, which issued by households in Kawangware Ward for domestic purposes. In the months of July and August 2017, a total sample of 112 samples of water were collected in the morning and evening. The results of samples from Gatina site show that the following parameters were above the KEBs drinking water standards: turbidity (x̄ =32.8; p=0.000), conductivity as EC (x̄ =601.3; p=0.000), total dissolved solids (x̄ =401.1; p=0.000), hardness as CaCo3 (x̄ =107.6; p=0.000), Sulphate as SO4 (x̄ =0.375; p=0.000), Nitrate as NO3 (x̄ =18.5; p=0.000), Phosphate as PO4 (x̄ =6.7; p=0.001), Lead as Pb (x̄ =0.19; p=0.000), Cadmium as Cd (x̄ = 0.04; p=0.000), Zinc as Zn (x̄ =0.20; p=0.000), Sodium as Na (x̄ =97.0; p=0.000) and Potassium as K (x̄ =25.5; p=0.000).  In the Kawangware site, the following parameters were found to be above the KEBs drinking water standards: pH (x̄ = 7.8; p=0.000), Conductivity( EC) (x̄ =966.3; p=0.000), Total dissolved solids (x̄ =603.1; p=0.000), Hardness as CaCo3 (x̄ =164.8; p=0.000), Sulphate (SO4) (x̄ =0.44; p=0.000), Nitrate ( NO3) (x̄ =18.4; p=0.000), Lead as Pb (x̄ =0.08; p=0.000), Iron as Fe (x̄ =0.18; p=0.001), Cadmium (Cd) (x̄ =0.04; p=0.000), Zinc (Zn) (x̄ =0.02; p=0.000) and Sodium ( Na) (x̄ =113.3; p=0.000). The Kabiro show that the following parameters were above the KEBs drinking water standards:  pH (x̄ = 8.1; p=0.002), Conductivity as EC (x̄ = 310.7; p=0.001), TDS (x̄ = 195.6; p=0.001), Hardness as CaCo3 (x̄ =13.8; p=0.001), Sulphate as SO4 (x̄ = 0.1; p=0.001), Nitrate as No3 (x̄ =17.9; p=0.001), Lead (Pb) (x̄ =0.20; p=0.001), Iron as Fe (x̄ =0.01; p=0.001), Cadmium (Cd) (x̄ =0.04; p=0.001), Zinc (Zn) (x̄ =0.01; p=0.001), Sodium (Na) (x̄ =73.3; p=0.001) and Potassium as K (x̄ =7.9; p=0.001). Therefore, the ground water from shallow wells in Kawangware is not safe for drinking due to elevated levels of nitrates, phosphates, turbidity, lead and cadmium levels which poses a great health risk to the public.